A tropical mechanism for Northern Hemisphere deglaciation - Rodgers, K; Lohmann, G; Lorenz, S; Schneider, R; Henderson, G (2003)
[1] We investigate the role of the tropics in the melting and reforming of the Laurentide ice sheet on glacial timescales using an atmospheric general circulation model. It is found that warming of tropical sea surface temperatures (SSTs) from glacial boundary conditions, as observed at the end of glacial periods, causes a large increase in summer temperatures centered over the ice sheet-forming regions of Canada. This highlatitude response to tropical change is due to relatively small changes in the circulation of the extratropical atmosphere, which lead to changes in the vertical profiles of temperature and moisture in the extratropical atmosphere. The maximum perturbation in the summer radiative balance over the Laurentide ice sheet (>25 W/m2) due to the changes in the local atmospheric water vapor inventory is much larger than that induced by glacial to interglacial changes in atmospheric CO2. These changes via an atmospheric bridge between the tropics and extratropics represent a mechanism for deglaciations which is consistent with timing constraints. In contrast, a cold perturbation to tropical SST for interglacial boundary conditions results in only very small changes in the delivery of water vapor to the Laurentide region, and therefore almost no cooling over the Canadian region. This implies that tropical SSTs could play a more important role in melting ice sheets in the Northern Hemisphere than in reforming them, possibly providing a mechanism which could help to explain the rapidity of deglaciation relative to glacial inception. © 2003 by the American Geophysical Union.